Magnesium hydridotriphenylborate [Mg(thf)6][HBPh3]2: a versatile hydroboration catalyst. Issue 89 (20th October 2016) - Mukherjee, Debabrata; Shirase, Satoru; Spaniol, Thomas P.; Mashima, Kazushi; Okuda, Jun
Abstract : Magnesium bis(hydridotriphenylborate), a solvent-separated ion pair [Mg(thf)6 ][HBPh3 ]2, is a versatile catalyst for hydroboration of polar unsaturated substrates including CO2 . Abstract : Magnesium bis(hydridotriphenylborate), isolated as a solvent-separated ion pair [Mg(thf)6 ][HBPh3 ]2, effectively catalyzed the hydroboration of several unsaturated substrates including CO2 .